Evaluation of the Effect of Dietary Manganese on the Intestinal Digestive Function, Antioxidant Response, and Muscle Quality in Coho Salmon - Dongwu Liu; Wenshuo Xie; Zhiling Xia; Ya Wang; Xinran Zhang; Qiuxiang Pang (Aquaculture Nutrition)
Manganese (Mn) is a nutritional element required for fish growth and physiology functions. In this study, we examined the effect of Mn on the intestinal digestive function, antioxidant response, and muscle quality in coho salmon (Oncorhynchus kisutch). Nine hundred salmons with initial weight approximately 0.35 g were fed with six isoproteic and isoenergetic diets formulated to contain 2.4, 8.5, 14.8, 19.8, 24.6, and 33.7 mg/kg Mn for 84 days. The result showed that the activity of trypsin and lipase was elevated, whereas α-amylase activity was not affected by various Mn diets in intestine. Dietary Mn elevated the activity of Mn-superoxide dismutase (Mn-SOD), total superoxide dismutase (T-SOD), glutathione peroxidase (GSH-PX), and catalase (CAT), but had no influence on copper/zinc-superoxide dismutase (Cu/Zn-SOD) in intestine. Dietary Mn at 8.5, 14.8, 19.8, 24.6, and 33.7 mg/kg enhanced the gene expression level of protein kinase B (Akt) and mammalian target of rapamycin (mTOR). In addition, the accumulation of Mn in muscle was enhanced with increasing levels of dietary Mn. Dietary Mn elevated the content of sodium (Na), potassium (K), magnesium (Mg), and calcium (Ca), but the content of iron (Fe) and Zn was decreased by dietary Mn in the salmon muscle. The content of fatty acids and amino acids was enhanced by various levels of dietary Mn in muscle. Moreover, a significant quadratic effect was observed on the texture of salmon muscle. The dietary Mn requirement was 16.9–25.7 mg/kg Mn to acquire the highest value of muscle texture using the quadratic regression model. The diets at 14.8 and 19.8 mg/kg Mn had a higher score of sensory evaluation for raw muscle. Our result showed that dietary Mn affected the intestinal digestion function and antioxidant response, which may further result in the change of muscle quality in coho salmon. The result will provide reference for detecting the effect of dietary micronutrients on the muscle quality of salmons.